Preoperative combined with intraoperative skin-surface warming avoids hypothermia caused by general anesthesia and surgery - Vanni, Simone Maria D'Angelo [UNESP]; Braz, José Reinaldo Cerqueira [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP]; Amorim, Rosa Beatriz [UNESP]; Rodrigues Júnior, Geraldo Rolim [UNESP] (Elsevier, 2003)
Study Objectives: To evaluate the effects of intraoperative skin-surface warming with and without 1 hour of preoperative warming, in preventing intraoperative hypothermia, and postoperative hypothermia, and shivering, and in offering good conditions to early tracheal extubation. Design: Prospective, randomized, blind study. Setting: Teaching hospital. Patients: 30 ASA physical status I and II female patients scheduled for elective abdominal surgery. Interventions: Patients received standard general anesthesia. In 10 patients, no special precautions were taken to avoid hypothermia. Ten patients were submitted to preoperative and intraoperative active warming. Ten patients were only warmed intraoperatively. Measurements and Main Results: Temperatures were recorded at 15-minute intervals. The patients who were warmed preoperatively and intraoperatively had core temperatures significantly more elevated than the other patients during the first two hours of anesthesia. All patients warmed intraoperatively were normothermic only at the end of the surgery. The majority of the patients warmed preoperatively and intraoperatively or intraoperatively only were extubated early, and none had shivering. In contrast, five unwarmed patients shivered. Conclusions: One hour of preoperative warning combined with intraoperative skin-surface warming, not simply intraoperative warming alone, avoided hypothermia caused by general anesthesia during the first two hours of surgery. Both methods prevented postoperative hypothermia and shivering and offered good conditions for early tracheal extubation. © 2003 by Elsevier B.V.
Keywords: Anesthesia; General; Hypothermia; Prewarming of skin surface; Shivering; Warming; Warming device; atracurium; fentanyl; isoflurane; midazolam; propofol; abdominal surgery; adult; body temperature; clinical article; clinical trial; controlled clinical trial; controlled study; core temperature; double blind procedure; endotracheal intubation; extubation; general anesthesia; health status; high temperature; human; hypothermia; intraoperative period; medical record; preoperative period; priority journal; prospective study; randomized controlled trial; sampling; shivering; skin surface; standard; teaching hospital; warming; Abdomen; Adult; Anesthesia, General; Body Temperature Regulation; Double-Blind Method; Heat; Humans; Intraoperative Care; Intraoperative Complications; Postoperative Complications; Preoperative Care; Prospective Studies; Skin Temperature